2008
DOI: 10.1007/s11869-008-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of particle size distributions of PAHs at Seoul, Korea

Abstract: The atmospheric size distributions of particulate polycyclic aromatic hydrocarbons (PAHs) up to 10 μm in diameter were measured at Seoul in the summer and winter of 2003. The concentrations of total PAHs were from 4.32 to 5.48 ng m −3 in summer and from 25.6 to 35.9 ng m −3 in winter, respectively. Majority of the PAHs concentrations were found on fine particles (D p <2.1 μm). The size distributions of individual PAH compounds were bimodal with the peaks in the 0.43-0.65-and 4.7-5.8-μm range in summer. In wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…As well, the shift of PAH and particulate matter (PM 10 ) size distributions peaks from 0.65 to 1.1 mm in summer to 1.1-2.1 mm in winter from vehicular sources in Seoul was attributed to PM 10 mass gain by absorption of water vapour (Lee et al, 2008). This observation supports the earlier suggestion that the entrainment of DPM particles containing PAHs in the nautical environment leads to the formation of hydrated particles.…”
Section: Article In Presssupporting
confidence: 83%
“…As well, the shift of PAH and particulate matter (PM 10 ) size distributions peaks from 0.65 to 1.1 mm in summer to 1.1-2.1 mm in winter from vehicular sources in Seoul was attributed to PM 10 mass gain by absorption of water vapour (Lee et al, 2008). This observation supports the earlier suggestion that the entrainment of DPM particles containing PAHs in the nautical environment leads to the formation of hydrated particles.…”
Section: Article In Presssupporting
confidence: 83%
“…7(1), [38][39][40][41][42][43][44][45][46][47]2013 0.95-1.5 μm and 3.0-7.5 μm . Lee et al (2008) also showed that the PM 10 size distribution should be bimodal with the peaks in the 0.65-1.1 μm and 4.7-5.8 μm size ranges, respectively, in Seoul urban areas. Furthermore, showed that the mean PM concentration was obtained in the particle fraction ⁄0.95 μm, accounting for 62% and 36% of total PM in an urban site in Greece during winter and summer.…”
mentioning
confidence: 90%
“…Seasonal variations can be exemplified by the study of Lee et al (2008) in which the PAH particle size distributions for summer were biomodal (raging between 0.43-0.65 and 4.7-5.8 µm) while those for winter were unimodal (range of 0.65-1.1 µm). Lack of a coarse fraction peak in winter is due to lower temperatures resulting to reduced gasparticle partitioning via volatilization.…”
Section: Particle Size Distribution Of Pahsmentioning
confidence: 99%